Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Guru Melalui Motivasi Guru Pada Kelompok Kerja Madrasah (KKM) 8 Kabupaten Pandeglang - Sulis Setianingsih; Ahmad Mukhlis; Khaeruman Khaeruman; Wahyu Wiguna (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Improving teacher performance is an important aspect of enhancing the quality of madrasah education. Teacher performance is not only determined by individual competence but is also influenced by leadership practices and organizational conditions. Therefore, transformational leadership and organizational culture are considered strategic factors in improving teacher work motivation and performance.This study aims to analyze the effect of transformational leadership and organizational culture on teacher performance, both directly and indirectly through teacher work motivation as a mediating variable. This study employed a quantitative approach using a survey method. The population consisted of teachers of Madrasah Tsanawiyah (MTs) affiliated with KKM MTs 8 in Pandeglang Regency, with a total sample of 134 respondents. Data were collected through questionnaires and analyzed using PLS-SEM with the assistance of SmartPLS. The results indicate that transformational leadership and organizational culture have a positive and significant effect on teacher work motivation and teacher performance. Based on these findings, it can be concluded that improving teacher performance can be optimized through transformational leadership and organizational culture that support teacher work motivation.